PERAN PENDIDIKAN BERBASIS LINGKUNGAN DALAM MEMBENTUK GENERASI BERKELANJUTAN - Ganti Ritauli Sianturi; Asni Susanti; Yulisna; Hadiyanto4 (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Environmental education plays an important role in shaping the character and knowledge of students. Amidst increasing environmental issues, environmental-based education is a significant factor influencing learning outcomes and individual behavior. This study explores the role of environmental-based education in building awareness and promoting sustainable health among early childhood. The method used is a qualitative approach with case study analysis in PAUD institutions that implement environmental-based curriculum. The results show that the integration of environmental education in the curriculum can improve children's knowledge, attitudes, and behavior towards the environment, contributing to the development of more effective educational programs for future environmental challenges. Keywords: Environmental Education, Environmental Awareness, Sustainable Health, Environmental-Based Curriculum, Environmental Behavior